2015
DOI: 10.1007/s00228-015-1872-5
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in VEGFA gene affect the antihypertensive responses to enalapril

Abstract: These findings suggest that polymorphisms in VEGFA gene may affect the antihypertensive responses to enalapril.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…Although PRKCA haplotypes did not significantly affect the responses to enalapril in the analysis including the total number of patients, we found that CTA haplotype is associated with worse responses to enalapril 20 mg/day. This finding is in line with previous studies showing that the effects of polymorphisms or haplotypes on the responses to antihypertensive drugs are more evident at higher doses [26,46,47]. Interestingly, the CTA haplotype includes the T and A alleles for the rs1010544 and rs16960228 polymorphisms, respectively, which are involved with worse responses to enalapril.…”
Section: Discussionsupporting
confidence: 91%
“…Although PRKCA haplotypes did not significantly affect the responses to enalapril in the analysis including the total number of patients, we found that CTA haplotype is associated with worse responses to enalapril 20 mg/day. This finding is in line with previous studies showing that the effects of polymorphisms or haplotypes on the responses to antihypertensive drugs are more evident at higher doses [26,46,47]. Interestingly, the CTA haplotype includes the T and A alleles for the rs1010544 and rs16960228 polymorphisms, respectively, which are involved with worse responses to enalapril.…”
Section: Discussionsupporting
confidence: 91%
“…International Journal of Hypertension 5 correlated with tumor stage and progression [29,30]. A recent study showed that polymorphisms in the VEGFA gene may affect the antihypertensive responses to enalapril [31]. In particular, A/A genotype at the rs699947 site is associated with a more intense decrease in blood pressure in response to enalapril, underlying its protective effect in hypertension, consistent with our results observed among rs699947, rs833061, and rs3025010.…”
Section: Discussionsupporting
confidence: 89%
“…Disruption of this gene in mice resulted in abnormal embryonic blood vessel formation, while allelic variants of this gene have been associated with microvascular complications of diabetes, atherosclerosis and the antihypertensive response to enalapril45. We previously reported a fibroblast growth factor ( FGF5 ) gene locus in association with BP10.…”
Section: Discussionmentioning
confidence: 99%